2018
DOI: 10.3390/ijms19010289
|View full text |Cite
|
Sign up to set email alerts
|

BRAF and MEK Inhibitors Influence the Function of Reprogrammed T Cells: Consequences for Adoptive T-Cell Therapy

Abstract: BRAF and MEK inhibitors (BRAFi/MEKi), the standard treatment for patients with BRAFV600 mutated melanoma, are currently explored in combination with various immunotherapies, notably checkpoint inhibitors and adoptive transfer of receptor-transfected T cells. Since two BRAFi/MEKi combinations with similar efficacy are approved, potential differences in their effects on immune cells would enable a rational choice for triple therapies. Therefore, we characterized the influence of the clinically approved BRAFi/MEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…As described earlier, the use of immune checkpoint inhibitors in combination with a BRAF inhibitor + MEK inhibitor appears to be effective but is associated with a high rate of toxicity [ 194 ]. Other potential immune-targeted therapies undergoing preclinical investigation include adoptive T-cell therapy [ 171 , 248 , 249 ], dendritic cell vaccination [ 250 ], and combining BRAF inhibitor treatment with a toll-like receptor 7 agonist (e.g., imiquimod) [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…As described earlier, the use of immune checkpoint inhibitors in combination with a BRAF inhibitor + MEK inhibitor appears to be effective but is associated with a high rate of toxicity [ 194 ]. Other potential immune-targeted therapies undergoing preclinical investigation include adoptive T-cell therapy [ 171 , 248 , 249 ], dendritic cell vaccination [ 250 ], and combining BRAF inhibitor treatment with a toll-like receptor 7 agonist (e.g., imiquimod) [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nivolumab, an anti-PD-1 Ab, significantly prolonged the survival in patients with metastatic melanoma, and is known to induce long-acting antitumor immune effects. 2 Because the release of tumor-specific antigen is necessary for the induction of the antitumor immune response, 4 DT before or after the administration of nivolumab may augment the immune response against melanoma. 4,5 Tumor-associated macrophages (TAM) create an immunosuppressive microenvironment together with other suppressor cells in the tumor-bearing host, and have been detected in various skin cancers including melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…2 Because the release of tumor-specific antigen is necessary for the induction of the antitumor immune response, 4 DT before or after the administration of nivolumab may augment the immune response against melanoma. 4,5 Tumor-associated macrophages (TAM) create an immunosuppressive microenvironment together with other suppressor cells in the tumor-bearing host, and have been detected in various skin cancers including melanomas. 6 Moreover, as Gordon et al 7 reported, TAM in melanoma express PD-1, and the blockade of PD-ligand 1/PD-1 signaling induces M1-like responses, leading to an antitumor immune response in melanomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A special safety measurement to circumvent prolonged autoimmunity induced by an on-target/ off-tumor reaction of the CAR is the introduction of the CAR by mRNA electroporation (n = 5, 2.6%; Figure 4). We have previously demonstrated that transient transfection of T cells with CARs using mRNA electroporation might be an effective and safe tool in cancer immunotherapy [121,[216][217][218][219][220]. The electroporation procedure is based on complex physicochemical mechanisms leading to plasma membrane perforation upon application of electric fields allowing for subsequent entry of mRNA into the cytosol [221].…”
Section: Safety Measurements To Control Negative Effects Of Car-t Celmentioning
confidence: 99%